Multi-Species Genomics-Enabled Selection for Improving Agroecosystems Across Space and Time - Wolfe, Marnin D.; Jannink, Jean-Luc; Kantar, Michael B.; Santantonio, Nicholas (Frontiers in Plant Science, 2021)
Plant breeding has been central to global increases in crop yields. Breeding deserves praise for helping to establish better food security, but also shares the responsibility of unintended consequences. Much work has been done describing alternative agricultural systems that seek to alleviate these externalities, however, breeding methods and breeding programs have largely not focused on these systems. Here we explore breeding and selection strategies that better align with these more diverse spatial and temporal agricultural systems.